2012
DOI: 10.1007/s12630-012-9781-x
|View full text |Cite
|
Sign up to set email alerts
|

Should intraoperative cell-salvaged blood be used in patients with suspected or known malignancy?

Abstract: Should intraoperative cell-salvaged blood be used in patients with suspected or known malignancy? Les cellules sanguines épargnées en peropératoire doivent-elles être réutilisées chez des patients ayant des processus malins connus ou suspectés? Abstract Purpose Intraoperative cell salvage (ICS) is used as an alternative to allogeneic blood transfusion in an attempt to avoid or minimize the risks associated with allogeneic blood. Intraoperative cell salvage is generally avoided in surgeries where malignancy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 82 publications
0
20
0
7
Order By: Relevance
“…Intraoperative cell salvage has been avoided in malignant resections for fear of promoting metastasis. A recent meta‐analysis failed to show an association with cancer recurrence, and is corroborated by evidence that modern cell salvage devices filter malignant cells. Although there is increasing evidence that intraoperative cell salvage is safe in cancer surgery, it can be costly when used for patients who are unlikely to require a RBC transfusion, and preoperative identification of appropriate patients would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative cell salvage has been avoided in malignant resections for fear of promoting metastasis. A recent meta‐analysis failed to show an association with cancer recurrence, and is corroborated by evidence that modern cell salvage devices filter malignant cells. Although there is increasing evidence that intraoperative cell salvage is safe in cancer surgery, it can be costly when used for patients who are unlikely to require a RBC transfusion, and preoperative identification of appropriate patients would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Leukodepletion filters appear to be an effective method for removal of malignant cells from ICS blood. 185 More recent non-randomised studies in urological cancer surgery and metastatic spinal surgery have shown ICS to decrease the need for allogeneic RBC transfusion with no apparent risk of decreased long-term survival from an oncological perspective. [186][187][188] Contamination of the surgical field (e.g.…”
Section: Cell Salvage Recommendationsmentioning
confidence: 99%
“…The use of LDFs has not been shown to be associated with either bradykinin or leukotriene generation in cell‐salvaged blood . Cell salvage may reduce or eliminate exposure to allogeneic blood, which has been associated with immunosuppression and cancer recurrence . One major disadvantage of LDFs is that the rate of flow through them is considerably slower, and therefore clinicians may need to assess the benefit of quicker transfusion without a LDF vs. its use.…”
Section: Cancer Surgerymentioning
confidence: 99%